Re-evaluation of population-level protection conferred by a rotavirus vaccine using the 'fried-egg' approach in a rural setting in Bangladesh. Issue 40 (24th September 2021) - Aziz, Asma Binte; Zaman, K.; Kim, Deok Ryun; Park, Ju Yeon; Im, Justin; Ali, Mohammad; Ahmmed, Faisal; Islam, Md Taufiqul; Khanam, Farhana; Chowdhury, Fahima; Ahmed, Tasnuva; Hoque, Masuma; et al.
Highlights: The "fried-egg" analytic approach was applied to a cluster randomized trial (CRT). Overall analysis failed to reveal rotavirus vaccine (RV) herd protection. Same approach unmasked herd protection of other enteric vaccines failed for RV. Abstract: Background: Vaccine herd protection assessed in a cluster-randomized trial (CRT) may be masked by disease transmission into the cluster from outside. However, herd effects can be unmasked using a 'fried-egg' approach whereby the analysis, restricted to the innermost households of clusters, 'yolk', creates an insulating 'egg-white' periphery. This approach has been demonstrated to unmask vaccine herd protection in reanalyses of cholera and typhoid vaccine CRTs. We applied this approach to an earlier CRT in Bangladesh of rotavirus vaccine (RV) whose overall analysis had failed to detect herd protection. Herein we present the results of this analysis. Methods: In the study area, infants in 142 villages were randomized to receive two doses of RV with routine EPI vaccines (RV villages) or only EPI vaccines (non-RV villages). We analyzed RV protection against acute rotavirus diarrhoea for the entire cluster (P100) and P75, P50, P25 clusters, representing 75%, 50% and 25% of the innermost households for each cluster, respectively. Results: During 2 years of follow-up, there was evidence of 27% overall (95 %CI: 7, 43) and 42% total protection (95 %CI: 23, 56) in the P100 cluster, but it did not increase when moved in smaller yolks. There was no evidence of indirect vaccine protection in the yolks at any cluster size. Conclusion: Our reanalysis of the CRT using the fried- egg approach did not detect RV herd protection. Whether these findings reflect a true inability of the RV to confer herd protection in this setting, or are due to limitations of the approach, requires further study.